Sub-national structures matter when evaluating physical activity promotion: Lessons from Germany. (30th September 2020) - Forberger, S; Gelius, P; Messing, S; Volf, K; Kelly, L; Taylor, S; Zukowska, J; Lakerveld, J; Woods, C
Abstract: Background: Public policies are increasingly acknowledged as important part of promoting physical activity (PA). However, especially in states with sub-national administrative structures such as Germany, national and sub-national approaches differ considerably. In Germany, sport for all (SfA) promotion is mostly organized at sub-national level, which is usually not covered in national evaluations. Knowledge of these structures helps to understand national outcomes, enables comparisons and learning within and between countries, and assists in identifying support structures for effective PA promotion. Methods: Data were collected in the PEN Policy Evaluation Network project. In addition to the WHO HEPA PAT, a questionnaire was sent to the sports representatives of the 16 federal states. Responses of 11 state representatives were included and overarching issues were identified using inductive thematic analysis. Results: PA promotion in Germany is organized in three areas: SfA, professional sports and school sports. SfA promotion at sub-national level is assigned to different administrative bodies (ministries, senate administration, state chancellery) and policy areas: culture, health and care, home affairs with various aspects, education, social affairs and family. The priorities of the federal states are more diverse and specific compared to the national level. There is an overlap in the topics: urban planning, cycling, health prevention and targeting children. Cooperation mechanisms and partners vary between federal states, but some partners are active at sub-national and national level. Conclusions: The results provide an insight into the complexity of PA and especially SfA promotion at sub-national level in Germany. Our results suggest that a broader range of approaches is used in the 16 German states than national overviews would suggest. These particularities must be taken into account when assessing and comparing the results from different countries. Key messages: The promotion of SfA at German sub-national level is much more diverse than represented at national level evaluations. Knowledge of sub-national structures enables the understanding of national outcomes, the promotion of cross-national learning and the identification of supportive structures for effective PA promotion.